A further generalized thickness-dependent non-Fickian moisture absorption model using plain woven epoxy composites. (August 2018) - Johar, M.; Kang, H.S.; Chong, W.W.F.; Wong, K.J.
Abstract: Mechanical performance of composite material is widely known to be susceptible to moisture attack. In order to determine the extent of moisture attack, the paper aims to generalize a thickness-dependent moisture absorption model for fiber reinforced composites. For this study, moisture absorption tests were conducted for woven glass/epoxy (2-ply and 6-ply) and woven carbon/epoxy (4-ply and 6-ply) composites, submerged in distilled water at 60 °C up to 94 days. From the measured moisture uptake behavior of the tested materials, a correlation function, linking normalized non-Fickian parameters and normalized laminate thicknesses, was derived to describe moisture absorption behavior of the tested composite materials using fictitious Fickian curve. To characterize non-Fickian moisture absorption behavior of composite materials, the derived correlation function suggested that only two arbitrary materials with different laminate thicknesses would suffice. Such correlation function could prove to ease the characterization of thickness-dependent non-Fickian moisture uptake behavior of fiber reinforced composites. Graphical abstract: Image 1 Highlights: The woven fiber composites exhibited non-Fickian moisture absorption behavior. The apparent diffusivity of glass was an order higher than carbon/epoxy composite. The apparent Fickian maximum moisture content was similar in both composites. Each normalized non-Fickian parameter could be fitted by a unique model. Two arbitrary thicknesses were sufficient to implement the model.